Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Expand the following:
a) x(x + 6)
b) x(5x - 1)
c) 3x(6x + 5)
d) 4x(2x – 3y)​


Sagot :

Answer:

a) x(x + 6)  = x · x + x · 6 = x² + 6x

b) x(5x - 1)  = x · 5x - x · 1 = 5x² - x

c) 3x(6x + 5)  = 3x · 6x + 3x · 5 = 18x² + 15x

d) 4x(2x – 3y)​ = 4x · 2x - 4x · 3y = 8x²-12xy